Influence of charge balance and microcavity effects on resultant efficiency of organic-light emitting devices - Choulis, Stelios A.; Krummacher, Benjamin C.; Mathai, Mathew K. (My University, 2006)
The contribution of charge balance and optical microcavity effects in solution processed OLEDs cannot be easily quantified due to the absence of a well defined location for the emission zone. In this paper, we study the device efficiency of a solution processed blue electrophosphorescent OLED where the relative electron-hole balance is varied by means of molecular doping with an electron transport material. Changes in the electroluminescent spectra for the device series indicate the presence of optical microcavity effects, which we quantify by means of optical simulation. Furthermore, this enables us to factor out the contribution of microcavity effects on device efficiency enabling the quantification of the charge balance effect on device performance
Keywords: Light emitting diodes; Computer simulation; Phosphorescence